PENGARUH LITERASI WAKAF TERHADAP MINAT MASYARAKAT MUSLIM DALAM WAKAF PRODUKTIF - Rahfi, Alif Dihza (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the influence of waqf literacy on the productive waqf interest of Muslim communities in Malang City, as well as to explore the role of control variables such as gender, age, and income in this relationship. A quantitative approach was employed using purposive sampling to select a sample of 100 respondents from the Muslim community in Malang City. Data were collected through questionnaires focusing on measuring waqf literacy and productive waqf interest. Data analysis involved simple regression to test the relationship between waqf literacy and productive waqf interest, and hypothesis testing to examine the significance of control variables. The results indicate that waqf literacy significantly influences productive waqf interest (β = 0.295, p < 0.001). Control variables, such as gender dan income also affect productive waqf interest, with males showing higher interest compared to females. Meanwhile, Age did not significantly influence productive waqf interest in this study. This study provides valuable insights into the factors influencing community participation in productive waqf, with practical implications for the development of inclusive education and socialization programs tailored to the needs of the Muslim community in Malang City.